Demand pull and technology push effects in the quality ladder model - Manfred Stadler (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2000)
This paper extends the standard quality ladder model of innovation and quality growth by allowing for heterogeneous industries. This enables us not only to deal with the Schumpeterian hypothesis about market power and innovation, but also to analyze industry specific demand pull and technology push effects. In accordance with the empirical evidence, we show that perspective of large market power, favorable technological opportunities and high demand expectations as well as the economy-wide endowment with qualified labor, unambiguously spur innovative activity.
urn:nbn:de:bsz:21-opus-21025
Keywords: L16; O33; 330; Innovative Activities; Demand Pull; Technology Push; Endogenous Growth; Endogener technischer Fortschritt; Produktqualität; Konsumtheorie; Innovationswettbewerb; Technischer Fortschritt; Industrieökonomik; Neue Wachstumstheorie; Theorie